(untitled) (Communications in Computational Chemistry, 2018)
The prescription of sofosbuvir tablets was screened to select the best prescription proportions. Methods: According to the prescription technology of foreign listed tablets “sovaldi®”, experiments of diluents, disintegrating agents, binders, lubricants and coating process were investigated, including the stability study of self-made samples and reference tablets under the conditions of high temperature, high humidity and illumination. We aimed to screen a reasonable prescription process. Results: Prescription process was ultimately determined including: sofosbuvir 400 mg, mannitol 360 mg, microcrystalline cellulose 360 mg, cross-linked sodium carboxymethyl cellulose 60 mg, magnesium stearate 14 mg, gum arabic 6 mg, opadry film coating powder 36 mg, and chose purified water as a binder. Conclusion: The determined prescription process was stable, and the production process was not harsh, it was suitable for scale-up production. The results of stability study and the dissolution behavior in vitro were similar to those of commercial products, so the prescription is design reasonably.